Buteyko Breathing Technique Effectively Improves Cardiorespiracy Endurance in Students - Kusumaningtyas, Mei; Handari, Herdianty K (Indonesian Journal of Medicine, 2024)
Background: As many as 51.32% of students from the Department of Physiotherapy at the Health Polytechnic of the Ministry of Health fell into the category of cardiorespiratory endurance (VO2max) less than normal. The VO2max value is influenced by breathing, physical activity and hemoglobin levels. There has not been much research on the influence of breathing without physical activity, so it is necessary to conduct research on the influence of breathing on cardiorespiratory endurance. The aim of this research was to determine the effect of Buteyko Breathing Technique on cardiorespiratory endurance. Buteyko Breathing Technique can significantly increase cardiorespiratory endurance. The breath-holding effect of the Buteyko Breathing Technique is the condition of maintaining high carbon dioxide levels all the time which can lower blood pH, causing more oxygen to be released into the tissues and cardiorespiratory endurance to increase. Subjects and Method: Randomized Control Trial research design, Buteyko Breathing Technique treatment group (n=29) and group II was the control group (n=30). Havard Step Test research measuring tool. The research subjects were students majoring from the Department of Physiotherapy at the Health Polytechnic, Ministry of Health, Surakarta. Results: The results of the paired sample t test in the treatment group obtained a value of p=0.027 (p<0.05), meaning that Buteyko Breathing Technique can increase cardiorespiratory endurance, while in the control group, a value of p=0.425 (p>0.05) was obtained, meaning there was no change in cardiorespiratory endurance. in the control group.        Conclusion: Buteyko Breathing Technique can significantly increase cardiorespiratory endurance.